Морфологическое обоснование целесообразности использования самоадаптирующихся машинных файлов в эндодонтической практике (Эндодонтия Today)
Basing on the lab and clinical material the benefits of the self-adapted rotary files in root canals with complex anatomical shape are demonstrated.